Xanthohumol from hop cones (Humulus lupulus L.) prevents ADP-induced platelet reactivity. (1st January 2017) - Luzak, Boguslawa; Kassassir, Hassan; Rój, Edward; Stanczyk, Lidia; Watala, Cezary; Golanski, Jacek
Abstract: Hop cones ( Humulus lupulus L.), very rich source of phenolic compounds, possessing anticancer, antioxidant and anti-inflammatory activities, are considered as beneficial diet ingredients improving human health. In this study, the antiplatelet action of xanthohumol (XN), the principal flavonoid in hop cones, was investigated. XN significantly attenuated ADP-induced blood platelet aggregation (97.2 ± 35.7 AU for 6 μg/ml of XN vs . 120.4 ± 30.1 AU for 0.17% dimethyl sulfoxide (DMSO), p  < 0.001) and significantly reduced the expression of fibrinogen receptor (activated form of GPIIbIIIa) on platelets' surface (47.6 ± 15.8 for 1.5 μg/ml XN, 44.6 ± 17.3% for 3 μg/ml XN vs . 54.5 ± 19.2% for control or 43.3 ± 18.4% for 6 μg/ml XN vs. 49.7 ± 19.4% for 0.17% DMSO, p  < 0.05 or less). These findings suggest that the phenolic compounds originating from hops (XN) have a novel role as antiplatelet agents and can likely be used as dietary supplements in prophylactic approaches.